2023
DOI: 10.3390/plants12030510
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cannabis sativa Phytochemicals as Anti-Alzheimer’s Agents: An In Silico Study

Abstract: Cannabis sativa is a medicinal plant that has been known for years and is used as an Ayurvedic medicine. This plant has great potential in treating various types of brain diseases. Phytochemicals present in this plant act as antioxidants by maintaining synaptic plasticity and preventing neuronal loss. Cannabidiol (CBD) and Tetrahydrocannabinol (THC) are both beneficial in treating Alzheimer’s disease by increasing the solubility of Aβ42 amyloid and Tau aggregation. Apart from these therapeutic effects, there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Swiss Target Prediction ( http://www.swisstargetprediction.ch/ ) [ 27 ] made the prediction of compound-based targets. Similarity between the compound-based targets and database-based targets were used for further network pharmacological analysis and validation through AutoDock [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Swiss Target Prediction ( http://www.swisstargetprediction.ch/ ) [ 27 ] made the prediction of compound-based targets. Similarity between the compound-based targets and database-based targets were used for further network pharmacological analysis and validation through AutoDock [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…Flavonoids, categorized as plant secondary compounds, possess antioxidant, anti -amyloidogenic, and anti-inflammatory properties and regulate cell-signaling pathways. Their demonstrated acetylcholinesterase inhibitory activity makes them a hopeful candidate for AD treatment [ 20 ]. In addition, terpenoids have many biological activities, and researchers have focused their attention on its anti-cholinesterase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigations have examined the potential bene ts of cannabis in addressing neurodegenerative diseases that affect cognitive abilities [20][21][22][23][24][25][26]. Additionally, the neuroprotective effect of this plant is widely studied and proven [27].…”
Section: Introductionmentioning
confidence: 99%
“…Fadaka et al 22 used molecular docking to predict potential compounds from C. sativa for Alzheimer's therapy. On the other hand, Patil et al 23 used three different molecular docking programs and concluded, as a first approximation, that THC, cannabinol (CBN), and cannabidiorcol would have some inhibitory effect on the enzymes AChE and BuChE (butyrylcholinesterase), which act as molecular targets of AD.…”
Section: Introductionmentioning
confidence: 99%